Contributos (antropo)metodológicos para um projecto social de cidade - Marluci Menezes (Ciências Sociais Unisinos)
The importance of the socio-cultural dimensions of the urban space is taken for granted in many of the current views of urban intervention and management. However, once in the field, the relevance of these dimensions is not always taken into account in an adequate manner, thus compromising a more effective accomplishment of aims. Some detected deficiencies are of a methodological nature and related to the way work proposals are conceived. The paper stresses three difficulties: emphasis on the contexts problems and minimization of their potentialities; need to render the socio-cultural diagnosis more operational; specific drawbacks of an interdisciplinary and multidimensional work. As an attempt to contribute to the overcoming of such difficulties, two notions are emphasized: project, understood as a strategy of invention or creation of a new sociospatial order as a cultural, phenomenological and pragmatic expression; diagnosis, conceived in an interactive, dynamic and flexible way. Finally, the author advocates the pertinence of investing in a project culture